A case-control study of occupational risk factors for laryngeal cancer. Issue 12 (December 1992) - Wortley, P; Vaughan, T L; Davis, S; Morgan, M S; Thomas, D B
Abstract : To determine whether specific jobs and occupational exposures are associated with laryngeal cancer lifetime occupational histories from a population-based case-control study in western Washington were examined. The study included 235 cases diagnosed between September 1983 and February 1987, and 547 controls identified by random digit dialing. After controlling for alcohol use, cigarette smoking, age and education, significantly increased risks were found for painters in construction (odds ratio (OR)) = 2.8, (95% confidence interval (95% CI) 1.1-6.9), supervisors and miscellaneous mechanics (OR = 2.3, 95% CI 1.1-4.8), construction workers (OR = 3.4, 95% CI 1.4-8.1), metalworking and plastic working machine operators (OR = 2.6, 95% CI 1.3-4.9) and handlers, and equipment cleaners and labourers (OR = 1.5, 95% CI 1.0-2.2). Allowing for a 10 year induction and latent period did not have a consistent effect on the associations. Potential exposures to asbestos, chromium, nickel, formaldehyde, diesel fumes, and cutting oils were assessed by using a job exposure matrix developed for this study. Three measures of exposure were examined–namely, peak, duration, and an intensity weighted exposure score. No significantly raised risks were seen, although increased risk was suggested among those exposed long term to formaldehyde in jobs with the highest exposures.